# math

posted by .

How do I use the quotient of powers property to show that zero to the zero power is undefined?

• math -

Think of x^n = (x^(n+1)) / x

so if x^1 =x, then x^0 = (x^1) / x = x / x =1

If x = 0 then: 0^1 = 0, so x ^ 0 = 0 / 0

now x / n heads towards (positive or negative) infinity as n becomes closer to 0.
As infinity is not a number, x / 0 has no numeric solution.

• math -

thanks-

## Similar Questions

the derivative of 2x^e is zero right or no?
2. ### domain

Find the domains of f and f' 1, f(x) = xe^x 2. f(x) = x^(3/5) 3. f(x) = x/(x-2) TIA 1) R 2) It's the interfal from zero to infinity for f but for f' it is this inteval with zero excluded, because unlike f, f' is singular at zero. 3) …

Explain why the slope of a horizontal line is zero, and the slope of a vertical line is undefined. The slope is the tangent of the enclosed angle. Tan = vertical side divided by horizontal side. With a horizontal line, the verticle …
4. ### math,algebra

Use the five properties of exponents to simplify each of the following expressions (y^5)^3(y^3)^2 divided by (y^4)^4 can someone show me how to solve these types of problems (y^5)^3= y^15 multiply the powers (y^3)^2=y^6 multiply the …

6. ### math

how am i supposed to use the quotient of powers property to show that zero to the zero power is undefined?
7. ### ALGEBRA

Can anyone explain this in 50 words why the equation turns out like it does?
8. ### Kate

ok I was doing this problem cos^-1 (0) and was like oh that would be pi/2 but then I thought about it some and decided that even though it's right it can't possibly be... if tan(pi/2) = the first derrivative of a vertical line = undefined …
9. ### math

use the given zero to find the remaining zeros of the function: F9x)=x^3-5x^2+4x-20; zero:2i I don't get it. Can someone please show me what to do with this?
10. ### algebra

Want to make sure I am doing this correctly. Use the Intermediate Value Theorem for polynomials to show that the polynomial function f(x)has zero between the numbers given. f(x)=3x^2-x-4 ; 1 and 2 3(1)^2-1-4= - 2 below zero 3(2)^2-1-4= …

More Similar Questions